Method for regulating and controlling crystal face growth in perovskite crystallization process and application of method in preparation of solar cell
By doping chloroformamidine hydrochloride in the perovskite precursor solution, the perovskite crystallization process is regulated, and the poor crystallization and defects of perovskite solar cells are solved, and efficient perovskite thin film crystallization and stability are achieved, which significantly improves the photoelectric performance and stability of solar cells.
Patent Information
- Application Number
- CN202411596341.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-11
AI Technical Summary
Perovskite solar cells face problems such as poor crystallinity, charge recombination loss caused by defects, charge transfer barriers caused by energy level mismatch, and poor environmental tolerance, which affect their photoelectric performance and stability.
By doping chloroformamidine hydrochloride into the perovskite precursor solution, the crystal surface growth during perovskite crystallization is regulated, and the selective growth of perovskite crystals along the (001) crystal surface is induced, the crystal quality is improved and the defect is reduced.
It improves the crystal quality and stability of perovskite films, reduces film defects, inhibits non-radiative recombination, and significantly improves the photoelectric performance and stability of perovskite solar cells.
Smart Images

Figure CN119546147A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of perovskite solar cells, and in particular relates to a method for regulating crystal face growth during perovskite crystallization and an application thereof in preparing solar cells. Background Art
[0002] Due to the continuous improvement of optoelectronic performance and stability, carboxamidinium-based perovskite solar cells have aroused great interest in industry and academia, and have shown great potential in actual commercialization. However, perovskite solar cells still face many challenges. The poor crystallinity of perovskite solar cells, charge recombination losses caused by defects, charge transfer barriers caused by energy level mismatch, and poor environmental tolerance have brought severe challenges to the further improvement of optoelectronic performance and commercial development. Therefore, improving crystallization performance, reducing defect state density, optimizing energy band alignment, and improving wet-heat stability are of great significance to obtain high-performance perovskite solar cells.
[0003] In general, traditional solution-based methods often have difficulty controlling the nucleation and crystal growth processes during the formation of perovskite films, resulting in reduced film uniformity, increased grain boundaries, non-radiative recombination centers, and unnecessary ion migration. It is necessary to find effective methods to regulate the precursor chemical synthesis so that it can be fully converted into the photoactive α phase, regulate crystallization, and suppress the appearance of the non-photoactive δ intermediate phase. The (001) and (111) planes in the α phase have been proven to be the two best performing crystal planes. Compared with the (111) plane, the (001) plane has more tightly connected atoms, exhibits lower surface energy, better coordination balance, and fewer defects. In order to achieve good growth of the (001) plane, especially crystal orientation regulation and passivation of internal and interfacial defects in the film, researchers have made various efforts. At the same time, the weak Pb-I bond of the (001) plane leads to structural distortion, and the high sensitivity of the (001) crystal plane to water molecules easily leads to severe moisture-induced degradation. Therefore, the stability of perovskite films dominated by the (001) plane is a problem that needs to be solved. Additive engineering has been shown to be an effective and simple strategy to optimize the quality of perovskite films, with advantages such as regulating the crystallization and growth of perovskite films, as well as passivating defects in the bulk and at the interface. To date, various additives have been used to tune perovskite layers, including inorganic salts, Lewis bases, polymers, and ionic liquids (ILs). All of these additives tend to interact with the metal cations (Pb 2+ Sn 2+ etc.) coordination, thereby delaying nucleation and significantly affecting crystal growth. The additives and A-site cations (FA + 、MA + The interaction between the (001) surface and its influence on the crystallization process of perovskite films need to be explored in detail. The use of additives to stabilize the (001) surface and thus reduce its degradation under high humidity and high temperature still requires further research. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a method for regulating crystal face growth during perovskite crystallization and its application in preparing solar cells.
[0005] To achieve the above purpose, the present invention adopts the following technical solution:
[0006] Chloroformamidine hydrochloride is doped into the perovskite precursor solution to regulate the crystal face growth during the perovskite crystallization process.
[0007] The final concentration of chloroformamidine hydrochloride in the perovskite precursor solution is 0.3-3.5 mg / ml. According to the stoichiometric ratio, cesium iodide (CsI), methylamine chloride (MACl), methylamine bromide (MABr), lead bromide (PbBr2), iodomethane (FAI), and lead iodide (PbI2) are weighed and dissolved in a mixed solvent to obtain a perovskite precursor solution with a concentration of 1.5M, and then chloroformamidine hydrochloride is added to obtain a perovskite precursor material.
[0008] The mixed solvent is a mixture of DMSO and DMF in a volume ratio of 4:1 to 6:1, and the molar ratios of cesium iodide (CsI), methylamine chloride (MACl), methylamine bromide (MABr), lead bromide (PbBr2), iodomethane (FAI), and lead iodide (PbI2) are 0.05:0.15:0.1:0.1:1.27:1.68.
[0009] Furthermore, the mixed solvent is a mixture of DMSO and DMF in a volume ratio of 4:1.
[0010] The perovskite precursor material is prepared by doping chloroformamidine hydrochloride into the perovskite precursor solution.
[0011] Application of the perovskite precursor material in the preparation of an inverse perovskite solar cell.
[0012] The perovskite precursor material is spin-coated on a substrate, and chlorobenzene anti-solvent is added dropwise during the spin-coating process.
[0013] Annealing at 80-120°C obtains a perovskite absorption layer.
[0014] During the spin coating of the perovskite precursor material, the spin coating was performed at a rotation speed of 4000 rpm for 20 to 40 seconds, and chlorobenzene anti-solvent was added dropwise at the 10th second.
[0015] From bottom to top, the inverse perovskite solar cell consists of a conductive glass substrate / hole transport layer / perovskite absorption layer / passivation layer / electron transport layer / metal electrode.
[0016] The preparation method of the inverse perovskite solar cell is as follows:
[0017] (1) cleaning the conductive substrate and spin coating a 2PACz solution on the surface of the conductive substrate and annealing to prepare a hole transport layer;
[0018] (2) spin coating a perovskite precursor material on the surface of the hole transport layer and performing an annealing treatment to obtain a perovskite absorption layer;
[0019] (3) adding phenethylammonium iodide solution dropwise onto the surface of the perovskite absorption layer to prepare a passivation layer;
[0020] (4) Spin coating PC on the surface of the passivation layer 61 BM solution, annealing, and then spin coating BCP solution to form an electron transport layer;
[0021] (5) Depositing silver onto the surface of the electron transport layer by thermal evaporation to form a metal electrode.
[0022] The concentration of the 2PACz solution is 0.5-1.0 mg / ml, the concentration of the phenethylammonium iodide solution is 2.0-2.5 mg / ml, and the concentration of the PC 61 The concentration of BM solution is 15-20 mg / mL, and the concentration of BCP solution is 0.5-1.0 mg / ml.
[0023] Furthermore,
[0024] S1. The transparent conductive glass substrate was cleaned with glass cleaner, deionized water, isopropyl alcohol, and acetone in sequence and dried with a nitrogen gun, and the conductive substrate was treated with a plasma cleaner for 15 minutes;
[0025] S2. The treated conductive glass substrate was transferred to a nitrogen glove box, spin-coated with a 2PACz solution, and annealed to obtain a hole transport layer;
[0026] S3. According to the stoichiometric ratio, cesium iodide (CsI), methylamine chloride (MACl), methylamine bromide (MABr), lead bromide (PbBr2), iodomethane (FAI), and lead iodide (PbI2) are weighed and dissolved in a mixed solvent to obtain a perovskite precursor solution, and then chloroformamidine hydrochloride is added to obtain a perovskite precursor material;
[0027] S4. Add a certain amount of perovskite precursor material to the surface of the conductive glass substrate containing the hole transport layer, spread the solution into a film by a spin coater, spin coat at a speed of 4000 rpm for 20 to 40 seconds, add 0.2 mL of chlorobenzene anti-solvent at the 10th second, and anneal the obtained film on a hot plate at 100°C for 50 minutes after spin coating to obtain a perovskite absorption layer;
[0028] S5. After the prepared perovskite absorption layer is cooled to room temperature, a layer of phenethylammonium iodide solution is spread on the surface by a spin coater (4000 rpm, spin coating for 20 seconds) to prepare a perovskite film passivation layer.
[0029] S6. Spin-coat the electron transport layer PC on the surface of the passivation layer at 2500 rpm 61 BM solution for 20 s, annealed on a 100 °C hot stage for 10 min, and then spin-coated with 1.0 mg / ml BCP solution at 4000 rpm to prepare the electron transport layer;
[0030] S7. Deposit silver onto the surface of the electron transport layer by thermal evaporation to form a metal electrode.
[0031] In the S1, the conductive substrate is ITO.
[0032] In S2, the 2PACz solution is spin-coated at a rotation speed of 3000 rpm for 30 seconds, and then placed on a hot plate at 100° C. for annealing for 10 minutes. The concentration of the 2PACz solution is 0.5-1.0 mg / ml, and the solvent is ethanol.
[0033] In S3, the concentration of the perovskite precursor solution is 1.5M, and the mixed solvent is a mixed solvent with a volume ratio of DMSO:DMF of 4:1 to 6:1. The molar ratio of cesium iodide (CsI), methylamine chloride (MACl), methylamine bromide (MABr), lead bromide (PbBr2), iodomethane (FAI), and lead iodide (PbI2) is 0.05:0.15:0.1:0.1:1.27:1.68.
[0034] In the S4, the amount of the perovskite precursor material added is 50 μL, and the anti-solvent is chlorobenzene, and the amount of the anti-solvent added is 200 μL.
[0035] In the S5, the concentration of phenethylammonium iodide (PEAI) is 2.0-2.5 mg / ml, the solvent is isopropanol, and the volume of the dropwise addition is 60 μL.
[0036] The S6, PC 61 The concentration of BM is 15-20 mg / mL, and the solvent is chlorobenzene. The concentration of BCP solution is 0.5-1.0 mg / mL, and the solvent is isopropanol.
[0037] In S7, the prepared perovskite device is placed in a mask with suitable specifications, and a vacuum coating machine is used to coat the perovskite device with a thickness of at least 1×10 -7 Pa under high vacuum conditions. By evaporating a 100nm silver electrode at a rate of , a complete perovskite solar cell device is obtained.
[0038] Working principle:
[0039] Aiming at the problem of poor crystallinity and high PbI2 in perovskite film, the present invention introduces ClFACl into the perovskite precursor solution, and generates active guanidine FA-Gua through the in-situ nucleophilic substitution reaction between ClFACl and FAI. The strong interaction between guanidine and perovskite components induces the selective growth of perovskite crystals along the preferred (001) crystal plane, increases the grain size, and effectively improves the crystallization quality of the perovskite film. During the annealing process, the active guanidine is mainly distributed at the perovskite grain boundary, passivates the grain boundary defects, and improves the stability of the perovskite film. Finally, due to the improvement of the perovskite crystallization quality, the film defects are reduced, the non-radiative recombination is effectively suppressed, the device efficiency is improved, and the stability is effectively improved.
[0040] Compared with the related art, the beneficial effects of the present invention are as follows:
[0041] The present invention uses chloroformamidine hydrochloride as a crystal face regulator of a perovskite precursor solution, and chloroformamidine hydrochloride is doped in the perovskite precursor solution, and an in-situ nucleophilic substitution reaction occurs between the chloroformamidine hydrochloride and FAI to regulate the crystal face selectivity of the perovskite crystal, induce the perovskite crystal to selectively grow along the (001) crystal face, improve the crystal quality of the perovskite film, reduce film defects, and inhibit non-radiative recombination, so that the perovskite film has good thermal stability and wet stability. The present invention specifically studies the nucleophilic substitution reaction between ClFACl and FAI, and proves the generation of active guanidine. The in-situ synthesized active guanidine structure is different from the guanidine structure in existing reports, contains more abundant active amino groups, and has a strong interaction with the perovskite component. The present invention systematically studies and confirms the regulation of the perovskite film formation process by the addition of ClFACl and the generation of active guanidine. The introduction of ClFACl homogenizes the nucleation of the precursor solution, inhibits the generation of impurities, promotes the transformation of the intermediate phase to the α phase, generates a highly crystalline perovskite film, and ultimately improves the photoelectric performance and stability of the device. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 It is ClFACl, FAI, ClFACl / FAI mixture 1 HNMR spectroscopy;
[0043] Figure 2 is the FTIR spectra of ClFACl and FAI / ClFACl mixture;
[0044] Figure 3 is the N1s XPS spectra of ClFACl and FAI / ClFACl mixture;
[0045] Figure 4 is the XRD spectra of FAI, ClFACl and FAI / ClFACl mixture;
[0046] Figure 5 It is the mixture of ClFACl and ClFACl / PbI2 1 H NMR spectrum;
[0047] Figure 6 are the FTIR spectra of ClFACl, ClFACl / PbI2, and FAI / ClFACl / PbI2 mixtures;
[0048] Figure 7 It is a microscopic picture of the effect of ClFACl additive on the nucleation process of perovskite wet film (Control is the reference, W / ClFACl is the addition of ClFACl, the same below);
[0049] Figure 8 It is a schematic diagram of the nucleation and crystallization process of perovskite film before and after optimization;
[0050] Fig. 9 This is a scanning electron microscope image, showing the effect of adding ClFACl on the surface morphology of the perovskite film;
[0051] Fig.10 This is a scanning electron microscope image, showing the effect of adding ClFACl on the cross-sectional morphology of the perovskite film;
[0052] Fig.11 is the grazing incidence small angle X-ray scattering image of the perovskite film before and after ClFACl optimization;
[0053] Fig.12 are the XPS spectra of the reference film and the perovskite film treated with ClFACl for a) Pb 4f, b) I 3d, and c) N 1s;
[0054] Fig.13 It is a comparison of the X-ray diffraction patterns and crystal plane ratios of the perovskite film before and after optimization;
[0055] Fig.14 are atomic force probe microscopy images of perovskite films before and after optimization;
[0056] Fig.15 a) Photographs of reference and ClFACl-treated perovskite films under 80°C heating aging conditions in ambient air (40-60% RH); b) SEM images of reference and c) ClFACl-treated perovskite films before and after heating in ambient air (40-60% RH); d) XRD patterns of reference and ClFACl-treated perovskite films stored in ambient air (~60% RH); e) XRD patterns of reference and f) ClFACl-treated perovskite films after storage in a N2 glove box heated at 60°C for 0-18 days;
[0057] Fig.16 is the transient fluorescence spectra of different device structures of perovskite films before and after optimization;
[0058] Fig.17 It is the JV curve of the solar cell after being tested by simulated light source before and after optimization. DETAILED DESCRIPTION
[0059] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Non-essential improvements and adjustments made to the present invention by technical personnel in the relevant field according to the above invention content should still belong to the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods not mentioned in detail are all process steps or preparation methods known to those skilled in the art.
[0060] The present invention utilizes the addition of chloroformamidine hydrochloride (ClFACl) to successfully regulate the nucleation and crystallization process of the perovskite layer, and realizes the selective regulation of the crystal plane of the perovskite crystal growth. In addition, the present invention proposes a detailed process of in-situ reaction of the additive and the A-site cation and crystallization regulation that has not been mentioned in previous documents, and systematically studies that after adding ClFACl, due to the strong interaction between ClFACl and FAI, the crystallization process is regulated to achieve the improvement of the perovskite crystal quality and the enhancement of the orientation, ultimately reducing the defects of the perovskite film and achieving the improvement of the device efficiency and stability.
[0061] Embodiment 1:
[0062] ClFACl was mixed with any of the individual components of the perovskite precursor: cesium iodide (CsI), methylamine chloride (MACl), methylamine bromide (MABr), lead bromide (PbBr2), formamidine iodide (FAI), and lead iodide (PbI2). It was found that after adding ClFACl to the FAI solution, the solution turned yellow. By mixing FAI, ClFACl, and FAI / ClFACl mixtures in DMSO-D6 solvent, the 1 The HNMR spectrum shows that -CH and -NH / ═NH hydrogen atoms in FAI have two proton peaks at 7.84 and 8.82 ppm, respectively, while the proton peak of ClFACl appears at 6.21 ppm. The FAI / ClFACl mixture has four proton peaks at 7.86, 8.68, 8.87 and 9.11 ppm, indicating that a strong chemical reaction occurs between FAI and ClFACl and a new compound is formed ( Figure 1). The integrated peak intensity ratio of these peaks is 1:1:2:2. Considering the deprotonation of organic amines and the potential of amides as guanidation agents, active guanidine (FA-Gua) is generated during the mixing of ClFACl and FAI, and its chemical structure is as follows:
[0063]
[0064] The strong interaction between ClFACl and FAI was further verified by Fourier transform infrared spectroscopy (FTIR) measurements and X-ray photoelectron spectroscopy (XPS). Figure 2 As shown, the ν of ClFACl C-Cl , ν C-N , ν N-H The stretching vibration peaks are located at 674.64, 1416.09 and 3020.86 cm -1 However, after mixing with FAI, the stretching vibration peaks shifted significantly to 622.46, 1343.71, and 3140.28 cm -1 At the same time, as shown in the XPS spectrum ( Figure 3 ), the N1s peak of the ClFACl / FAI mixture shifts slightly from 400.05 eV to a higher binding energy of 400.49 eV compared to pure ClFACl. Figure 4 As shown, compared with the X-ray diffraction (XRD) patterns of FAI and ClFACl, new characteristic peaks appeared in the ClFACl / FAI mixture at 11.46° and 22.67°, indicating the formation of FA-Gua with different crystal plane orientations.
[0065] In addition, the use of 1 The interaction between ClFACl and PbI2 was studied by HNMR and Fourier transform infrared spectroscopy. 1 HNMR spectrum see Figure 5 After mixing with PbI2, the proton peak of ClFACl shifted slightly from 6.21ppm to 6.19ppm, indicating that there is a coordination interaction between ClFACl and PbI2. As shown in the Fourier transform infrared spectroscopy results ( Figure 6 ), the ν of ClFACl in the ClFACl / PbI2 mixture (ClFACl:PbI2 molar ratio is 1:1) and the FAI / ClFACl / PbI2 mixture (FAI:ClFACl:PbI2 molar ratio is 2:2:1) N-H The stretching vibration peaks are from 3020.86cm -1 Move to 3137.36cm -1 and 3267.44cm -1 . ν N-HThe movement of is due to the formation of coordination compound between FA-Gua and PbI2, which confirms that the in situ synthesized FA-Gua and Pb 2+ The coordination effect of FA-Gua is stronger. Compared with PbI2 alone (Pb 4f is 143.58 eV and I 3d is 631.06 eV), ClFACl / PbI2 film shows lower Pb 4f binding energy (143.35 eV) and I3d binding energy (630.26 eV), while FAI / ClFACl / PbI2 further shows a blue shift (Pb 4f is 143.06 eV and I 3d is 630.01 eV). The further reduction in binding energy indicates that the intermolecular interaction between FA-Gua and PbI2 is strengthened after the in situ synthesis of active guanidine.
[0066] Embodiment 2:
[0067] Preparation of perovskite solar cells:
[0068] The etched conductive substrate ITO was cleaned and soaked in glass detergent, deionized water, isopropanol, and acetone for 15 minutes in sequence, and then purged and dried with a nitrogen gun; after being treated in a plasma machine (PLAMA) for 15 minutes, it was transferred to a glove box. The 0.5 mg / ml 2PACz solution (ethanol as solvent) prepared in advance was spin-coated on the ITO substrate at a speed of 3000 rpm for 30 seconds, and then annealed at 100°C for 10 minutes to obtain a hole transport layer.
[0069] According to the stoichiometric ratio, a certain amount of perovskite precursor raw materials were weighed: cesium iodide (CsI), methylamine chloride (MACl), methylamine bromide (MABr), lead bromide (PbBr2), iodomethane (FAI), and lead iodide (PbI2) in a molar ratio of 0.05:0.15:0.1:0.1:1.27:1.68, and dissolved in a mixed solvent of DMSO and DMF (volume ratio of 4:1), and dissolved by vortexing for 2 hours to obtain a 1.5M perovskite precursor clear solution, and chloroformamidine hydrochloride was added to the precursor solution to obtain a perovskite precursor material, so that the concentration of chloroformamidine hydrochloride in the precursor solution was 2.0 mg / ml.
[0070] Place the ITO substrate with the 2PACz hole transport layer on a spin coater, add 50 μL of perovskite precursor solution, spin coat at 4000 rpm for 30 seconds, and inject 0.2 mL of chlorobenzene antisolvent in the 10th second; after the spin coating, quickly transfer the wafer to a 100°C hot plate and heat for 50 minutes for annealing to obtain the perovskite absorption layer.
[0071] After the substrate with the perovskite was cooled to room temperature, 60 μL of 2.0 mg / ml isopropanol solution of phenylethylammonium iodide (PEAI) was added to the surface of the wafer by spin coating at 4000 rpm for 20 s to ensure the formation of a passivation layer.
[0072] Add 40 μL of the electron transport layer PC to the substrate after interface passivation. 61 BM solution (20 mg / mL, CB as solvent) was spin-coated at 2500 rpm for 20 s. After the spin-coating, it was annealed on a hot plate at 100°C for 10 min, and then 1.0 mg / ml BCP (solvent is isopropanol) was spin-coated at 4000 rpm for 20 s.
[0073] Silver is deposited on the surface of the electron transport layer by thermal evaporation (the prepared perovskite device is placed in a mask with suitable specifications, and a vacuum coating machine is used to deposit silver on the surface of the electron transport layer at least 1×10 -7 Pa under high vacuum conditions. By evaporating a 100nm silver electrode at a rate of , the prepared perovskite solar cell can be obtained).
[0074] Example 3
[0075] The difference between the preparation method and Example 2 is that the concentration of chloroformamidine hydrochloride in the precursor solution of Example 3 is 3.0 mg / ml.
[0076] Embodiment 4:
[0077] The difference between the preparation method and Example 2 is that the concentration of chloroformamidine hydrochloride in the precursor solution of Example 4 is 0.5 mg / ml.
[0078] Example 5
[0079] The difference between the preparation method and Example 2 is that the annealing temperature for preparing the perovskite absorption layer in Example 5 is 120°C.
[0080] Comparative Example 1:
[0081] The difference between the preparation method and Example 2 is that no chloroformamidine hydrochloride is added in Comparative Example 1, and the other preparation steps are exactly the same as those in Example 2.
[0082] Comparative Example 2:
[0083] The difference between the preparation method and Example 2 is that the chloroformamidine hydrochloride in Example 2 is replaced by pre-synthesized FA-Gua, and the other preparation steps are exactly the same as Example 2.
[0084] The difference in effect between Example 2 and Comparative Example 1 with or without adding ClFACl is as follows:
[0085] The perovskite films obtained in Example 2 and Comparative Example 1 were spin-coated by a spin coater and then observed under a microscope. Figure 7 As shown. Figure 7 It can be seen that the precursor perovskite solution containing ClFACl additive has more nucleation sites and the nucleation rate is greater than that of the precursor solution without ClFACl. Figure 8 The figure shows a schematic diagram of the nucleation and crystallization process of the reference film and the film containing ClFACl additive. Compared with the reference film, the strong interaction between the ClFACl additive and the perovskite promotes the formation of the α phase and induces the perovskite film crystal to grow along the (001) crystal plane.
[0086] Depend on Fig. 9 The surface morphology of the film shows that after ClFACl optimization, the crystallization quality of the perovskite film is significantly improved, the film surface is smoother, the grain size is larger, the grain boundary defects are reduced, and the residual PbI2 on the surface is reduced.
[0087] Depend on Fig.10 The cross-sectional morphology shows that compared with the reference film without ClFACl addition, the crystal growth orientation of the film optimized with ClFACl is significantly enhanced.
[0088] To further demonstrate the improvement of the orientation of thin film crystal growth, the present invention conducted a grazing incidence small angle X-ray scattering test ( Fig.11 ).Depend on Fig.11 It can be seen that the reference film of Comparative Example 1 has a weak out-of-plane vertical orientation crystallization signal and a strong PbI2 signal peak. After the ClFACl additive is optimized, the out-of-plane vertical orientation growth signal of the film is significantly enhanced, and the PbI2 signal peak is weakened, indicating that the optimized ClFACl induces the selective orientation growth of the crystal face. In order to further study the effect of in-situ synthesized guanidine on the final perovskite film, XPS tests were performed on the reference film of Comparative Example 1 and the perovskite film treated with ClFACl in Example 2. Fig.12 Compared with the peaks of the reference film (143.27 and 138.41 eV), the Pb 2+ 4f 5 / 2 and 4f 7 / 2 Peaks appeared at 142.91 and 138.04 eV, shifting to lower binding energy. In addition, two peaks at 141.69 and 136.77 eV belonging to Pb 0 The peak of FA-Gua and Pb 2+ The interaction between 3 / 2 、I 3d 5 / 2 The signals of N1s and N2s obviously shifted to lower binding energies after ClFACl treatment.
[0089] The present invention further explores the crystal quality and growth orientation of the perovskite film through XRD ( Fig.13 ) found that the crystal quality of the film was enhanced after adding ClFACl. (001) / I (022) The crystal face ratio increased significantly, the crystal showed a preferred growth along the (001) crystal face, the crystal orientation was significantly optimized, and the lead iodide signal intensity decreased, proving that the in situ generated active guanidine FA-Gua and Pb 2+ The coordination effect of is stronger and can inhibit the uncoordinated Pb atoms in the perovskite film, which is beneficial to improve the stability of the film. Fig.14 As shown, atomic force microscopy revealed that the roughness of the film decreased, proving that PbI2 on the film surface was reduced and the morphology was optimized.
[0090] The present invention further studies the effect of ClFACl on the stability of the perovskite crystal surface. In addition, Fig.15 a shows optical photographs of the film of Comparative Example 1 and the perovskite film treated with ClFACl of Example 2, which were heated at 80°C for 15 days under ambient conditions (40% to 60% RH). For the film of Comparative Example 1, a yellow phase appeared at the edge of the film after 9 days of heating, and the reference film was completely degraded after 15 days. However, the perovskite film treated with ClFACl still maintained a black phase after 15 days, with only slight degradation at the edge, showing excellent thermal stability and wet stability. Therefore, in order to systematically evaluate the effect of in-situ formed FA-Gua on the stability of perovskite films, the present invention recorded the evolution of the perovskite film morphology through scanning electron microscopy tests. As shown in Fig.15 As shown in Figs. b and c, after heating for 96 h in an ambient air at 80°C and a relative humidity (RH) of 40% to 60%, the perovskite film of Comparative Example 1 was severely degraded, and a large amount of white flaky PbI2 ( Fig.15 b), while the morphology of the perovskite film treated with ClFACl did not change much ( Fig.15 c). At the same time, as shown in the XRD results ( Fig.15 d), after 12 days of storage in ambient air conditions (25°C, ~60% RH), the PbI2 peak intensity of the reference film increased, the diffraction peak intensity at 14.2° attributable to α-FAPbI3 decreased significantly, and a diffraction peak at 11.8° attributable to the δ-FAPbI3 phase appeared, while the ClFACl-treated perovskite film maintained a stable black α-FAPbI3 phase. Further, the present invention explored the effect of ClFACl treatment on the thermal stability of the perovskite film, that is, heating at 60°C for 18 days in a nitrogen environment. Fig.15As shown in Figures e and 15f, the peak intensities of the (001) and (022) crystal plane diffraction peaks of the perovskite film in Comparative Example 1 are severely reduced, and the peak intensity of PbI2 is significantly increased. For the perovskite film treated with ClFACl, the changes in the (001) and (022) crystal planes are negligible, and the peak intensity of PbI2 is only slightly increased, indicating that the introduction of ClFACl can effectively inhibit the degradation of α-FAPbI3, thereby enhancing the thermal stability of the perovskite film.
[0091] In order to detect the changes in the defect state of perovskite films before and after ClFACl treatment, the transient fluorescence spectra of perovskite films on different substrates were tested and it was found that the lifetime of the film after ClFACl optimization on the glass substrate was extended. 61 The film life of the BM interface layer decreases, indicating that the defect state of the optimized film is reduced and the interface transmission capacity is enhanced ( Fig.16 ), and finally, due to the improvement of the crystal quality of the perovskite film, the reduction of grain boundary defects, and the regulation of lead iodide, the device performance and stability are significantly improved. The solar cells prepared in Examples 3-5 achieve the same optimization effect as Example 2.
[0092] In order to further verify the effect of in-situ synthesized FA-Gua on improving the photoelectric performance of perovskite solar cells, the present invention uses the reference perovskite solar cell device without adding ClFACl in Comparative Example 1, the perovskite solar cell device with chloroformamidine hydrochloride added in Example 2, and the perovskite solar cell device with pre-synthesized FA-Gua added in Comparative Example 2. The JV curve results after simulated light source testing are shown in the figure. Compared with the reference device without any additives, the device with pre-synthesized FA-Gua has a JV curve of 1.17×10-1.3×10-1. sc and V oc The improvement was not obvious, only FF increased to 81.12% and PCE increased to 24.15%. Furthermore, the device V of FA-Gua synthesized in situ by adding chloroformamidine hydrochloride oc The FF and FF were significantly increased to 1.20V and 82.77%, and the final PCE was significantly increased to 25.49%. + FA-Gua generated by the in-situ reaction has a stronger interaction with the perovskite components, which effectively improves the crystallization quality of the perovskite film, reduces the defects of the perovskite film, inhibits non-radiative recombination, and significantly improves the photoelectric performance and stability of perovskite solar cells.
[0093] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for regulating crystal face growth during perovskite crystallization, characterized in that: Chloroformamidine hydrochloride is doped into the perovskite precursor solution to regulate the crystal face growth during the perovskite crystallization process.
2. The control method according to claim 1, characterized in that: The final concentration of chloroformamidine hydrochloride in the perovskite precursor solution is 0.3-3.5 mg / ml.
3. The control method according to claim 2, characterized in that: According to the stoichiometric ratio, cesium iodide CsI, methylamine chloride MACl, methylamine bromide MABr, lead bromide PbBr2, iodomethane FAI, and lead iodide PbI2 are weighed and dissolved in a mixed solvent to obtain a perovskite precursor solution.
4. The control method according to claim 3, characterized in that: The mixed solvent is a mixture of DMF and DMSO in a volume ratio of 4:1 to 6:1, and the molar ratio of cesium iodide CsI, chloromethylamine MACl, bromomethylamine MABr, lead bromide PbBr2, iodoformamidine FAI, and lead iodide PbI2 is 0.05:0.15:0.1:0.1:1.27:1.
68.
5. A perovskite precursor material prepared by the control method according to any one of claims 1 to 4, characterized in that: The perovskite precursor material is prepared by doping chloroformamidine hydrochloride into the perovskite precursor solution.
6. An application of the perovskite precursor material according to claim 5, characterized in that: Application of the perovskite precursor material in the preparation of an inverse perovskite solar cell.
7. A perovskite absorption layer, characterized in that: The perovskite precursor material of claim 5 is spin-coated on the hole transport layer, an anti-solvent is added dropwise during the spin-coating process, and annealing is performed to obtain a perovskite absorption layer.
8. An inverted perovskite solar cell, characterized in that: The inverse perovskite solar cell comprises, from bottom to top, a conductive glass substrate / a hole transport layer / the perovskite absorption layer of claim 6 / a passivation layer / an electron transport layer / a metal electrode.
9. The inverted perovskite solar cell according to claim 8, characterized in that: (1) cleaning the conductive substrate and spin coating a 2PACz solution on the surface of the substrate and annealing to prepare a hole transport layer; (2) spin coating the perovskite precursor material according to any one of claims 1 to 4 on the surface of the hole transport layer and performing annealing treatment to obtain a perovskite absorption layer; (3) adding phenethylammonium iodide solution dropwise onto the surface of the perovskite absorption layer to prepare a passivation layer; (4) Spin coating PC on the surface of the passivation layer 61 BM solution, annealing, and then spin coating BCP to form an electron transport layer; (5) Depositing silver onto the surface of the electron transport layer by thermal evaporation to form a metal electrode.
10. The inverted perovskite solar cell according to claim 9, characterized in that: The concentration of the 2PACz solution is 0.5-1.0 mg / ml, the concentration of the phenethylammonium iodide solution is 2.0-2.5 mg / ml, and the concentration of the PC 61 The concentration of BM solution is 15-20 mg / mL, and the concentration of BCP solution is 0.5-1.0 mg / ml.
Citation Information
Patent Citations
Perovskite layer and preparation method thereof, perovskite silicon laminated solar cell and photovoltaic module
CN117979796A
Trans-perovskite solar cell, preparation method thereof and photovoltaic device
CN118019421A